2008
DOI: 10.1002/clen.200700139
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Zinc using Tea Factory Waste: Kinetics, Equilibrium and Thermodynamics

Abstract: In India, the annual production of tea is ca. 857,000 tonnes, which is 27.4% of the total world production. The amount of tea factory waste (TFW) produced per annum after processing is ca. 190,400 tonnes. TFW can be used as a low cost adsorbent for the removal of toxic metals from the aqueous phase. An investigation was carried out to study the feasibility of the use of TFW as an adsorbent for the removal of the heavy metal, zinc. Equilibrium, kinetic and thermodynamic studies were reported. The straight line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…Calculations showed that 0.243 of a total adsorption may be explained by the fast process (k 1 = 0.072 s -1 ), and 0.757 of the entire adsorption is contributed to a slow process (k 2 = 3.09 9 10 -3 s -1 ). Figure 1c presents the Weber-Morris plot on which the presence of linear region suggests that intraparticle diffusion might be one of these processes (Wasewar et al 2008;Płaziński and Rudziński 2009). However, the specific cellulose structure, for example, specific surface area\1 sq.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Calculations showed that 0.243 of a total adsorption may be explained by the fast process (k 1 = 0.072 s -1 ), and 0.757 of the entire adsorption is contributed to a slow process (k 2 = 3.09 9 10 -3 s -1 ). Figure 1c presents the Weber-Morris plot on which the presence of linear region suggests that intraparticle diffusion might be one of these processes (Wasewar et al 2008;Płaziński and Rudziński 2009). However, the specific cellulose structure, for example, specific surface area\1 sq.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Therefore, an inexpensive alternative to activated carbon can greatly increase the application of adsorption based method in various developing countries like Bangladesh. Materials such as tea waste, microbial biomass and straw etc., have already been tested generally as low-cost adsorbent (Aikpokpodion et al 2010;Amarasinghe and Williams 2007;Bhaina and D'Souza 2001;Cay et al 2004;Ingole and Bhole 2003;Kamsonlian et al 2011;Mahavi et al 2005;Wasewar 2010;Wasewar et al 2008). The use of waste materials as inexpensive adsorbent can have several additional advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The use of waste materials as inexpensive adsorbent can have several additional advantages. It is reported in general that tea waste is capable to trap heavy metals due to its highly porous structure with insoluble cell (Aikpokpodion et al 2010;Amarasinghe and Williams 2007;Cay et al 2004;Mahavi et al 2005;Wasewar 2010;Wasewar et al 2008). The functional groups present in tea waste also aid the trapping action.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra show a strong band at 3327.0 cm -1 attributed to either -OH or -NH groups [92,93]. But the band appears as two peaks, thus an indicator that it is most likely due to -NH groups [92,93].…”
Section: Resultsmentioning
confidence: 99%